2012
DOI: 10.1080/10255842.2012.739160
|View full text |Cite
|
Sign up to set email alerts
|

Influence of landmark and surgical variability on virtual assessment of total knee arthroplasty

Abstract: Given advances in recent years in imaging modalities and computational hardware/software, virtual analyses are increasingly valuable and practical for evaluating total knee arthroplasty (TKA). However, the influence of variabilities at each step in computational analyses on predictions of TKA performance for a population has not yet been thoroughly investigated, nor the relationship between these variabilities and expected variations in surgical practice. Understanding these influences is nevertheless essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Dai et al reported an average intra user variability of 2.9 mm and a maximum deviation of up to 6.3 mm (Dai et al 2014). In case of the clavicle, the correspondence quality is already within intra-user variability, therefore the manual identification of landmarks in the clavicle could be omitted.…”
Section: Discussionmentioning
confidence: 99%
“…Dai et al reported an average intra user variability of 2.9 mm and a maximum deviation of up to 6.3 mm (Dai et al 2014). In case of the clavicle, the correspondence quality is already within intra-user variability, therefore the manual identification of landmarks in the clavicle could be omitted.…”
Section: Discussionmentioning
confidence: 99%
“…However, manual selection of tibial landmarks is known to introduce errors that will compromise intra- and interrater reliability, because unpredictable human error and arbitrary choices are introduced. 6,41 This must be avoided to ensure consistent measurements. Therefore, for the new measurement presented in this article, we applied a standard method to create a reference frame for the bone slicing.…”
Section: Methodsmentioning
confidence: 99%
“…3,29,45,46 A validated and repeatable method to assess tibial torsion using CT or MRI is lacking and must be generated. 19,48 Ideally, such a method should ensure time efficiency for busy clinical settings, 27 minimize the high error associated with manual measurements, 6,43 and permit the generation of large, comparable data sets of normative and pathological alignment worldwide. The first aim of the present article is to define a reliable and clinically reasoned method for the calculation of tibial torsion that is automated, removing the potential for human error.…”
mentioning
confidence: 99%
“…The neutral rotational axis was defined as the line connecting the medial third of the tubercle and the center of the PCL attachment site (Insall's line), projected onto the resection plane of the two-dimensional (2D) digital image of the tibial plateau. 9,10 The mediolateral line (MLL) was drawn to be perpendicular to the Insall line in the 2D coordinate system. The anteroposterior line (APL) was drawn parallel to the Insall line and passed through the center of the MLL.…”
Section: Digital Implantation and Measurement Techniquesmentioning
confidence: 99%
“…6 Asymmetric tibial component designs have been developed; however, these twocomponent types cannot usually prevent overhang from the posteromedial or posterolateral zones during a well-aligned tibial component placement from the mediolateral and anterior aspects of the ideal component rotation. [7][8][9][10][11][12] Therefore, this study aimed to investigate (1) whether the tibial surface area exhibited any changes following tibial plateau cuts at different slope angles, (2) whether there was a change in the compatibility of the symmetric or asymmetric tibial baseplates with the tibial surface or overhang beyond bone margins following cuts at different slope angles, and (3) which slope cut angle could reduce the overhang or underhang. The hypothesis of our study was that during the implantation of the tibial component by providing rotational, mediolateral, and maximum coverage, overhang/underhang that may occur in the posterior cortex of the tibial component can be avoided by using different slope cut angles.…”
mentioning
confidence: 99%